NEUROLOGICAL COMORBIDITY IN MULTIPLE SCLEROSIS. LITERATURE REVIEW - Гичка, К. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
This article gives an overview of a literature devoted to the problem of the course of comorbid diseases in patients with multiple sclerosis (MS). The purpose of this work is to review the worl’s medical literature on the problem of comorbidity between MS and other neurological diseases, as well as to determine the impact of the neurological diseases and clinical characteristics of the main representative of demyelinating disorders.